Young's modulus and thermal conductivity of closed-cell, open-cell and inverse ceramic foams – model-based predictions, cross-property predictions and numerical calculations. Issue 6 (June 2018) - Pabst, Willi; Uhlířová, Tereza; Gregorová, Eva; Wiegmann, Andreas
Abstract: Numerical calculations of relative Young's modulus and thermal conductivity have been performed on computer-generated microstructures of wall-based (closed-cell) and strut-based (open-cell) cellular materials (foams) and inverse foams. The results are compared to rigorous upper bounds (Wiener-Paul, Hashin-Shtrikman), model-based predictions (power-law, exponential) and cross-property predictions (CPRs). It is shown that closed-cell foams exhibit higher property values than open-cell and inverse foams, Kelvin foams higher than random foams, and the difference between closed-cell and open-cell foams is larger than that between Kelvin and random foams. While the properties of closed-cell foams are higher than the power-law prediction, those of inverse and open-cell random foams are between the exponential and power-law predictions, and open-cell Kelvin foams follow the Gibson-Ashby power-law prediction for open-cell foams. The Pabst-Gregorová CPR is shown to predict Young's modulus with accuracy better than ±0.02 relative property units (better than any model-based relation and any other CPR).